Ireland in the Virginian sea : colonialism in the British Atlantic - Horning, Audrey J. (Published for the Omohundro Institute of Early American History and Culture, Williamsburg, Virginia by the University of North Carolina Press, 2013)
"In the late sixteenth century, the English started expanding westward, establishing control over parts of neighboring Ireland as well as exploring and later colonizing distant North America. Audrey Horning deftly examines the relationship between British colonization efforts in both locales, depicting their close interconnection as fields for colonial experimentation. Focusing on the Ulster Plantation in the north of Ireland and the Jamestown settlement in the Chesapeake, she challenges the notion that Ireland merely served as a testing ground for British expansion into North America. Horning instead analyzes the people, financial networks, and information that circulated through and connected English plantations on either side of the Atlantic. In addition, Horning explores English colonialism from the perspective of the Gaelic Irish and Algonquian societies and traces the political and material impact of contact. The focus on the material culture of both locales yields a textured specificity to the complex relationships between natives and newcomers while exposing the lack of a determining vision or organization in early English colonial projects"--